Physical Exercise Increases Cardiac Troponin (cTn) Levels as a Marker of Myocardial Infarction: A Systematic Review - Ayubi, Novadri; Wibawa, Junian Cahyanto; Aljunaid, Mohammed; Dafun, Procopio B.; Lesmana, Heru Syarli (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to analyze an indication of physical exercise on the increase of cardiac troponin (cTn) levels as a marker of myocardial infarction from the physiological perspective. Materials and methods. A search of journal databases including MEDLINE-Pubmed, Web of Science, Scopus, and Science Direct was used in this systematic review study. The inclusion criteria were papers that addressed cardiac troponin (cTn), physical activity, and myocardial infarction, and were published within the last five years. Using the databases Science Direct, Pubmed, and Web of Science, 83 recognized publications were found. For this systematic review, finally ten publications that fulfilled the requirements for inclusion were chosen and examined. This study evaluated standard operating procedures using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Results. This systematic review reports that physical exercise has been found to increase cardiac troponin (cTn) levels as a marker of myocardial infarction, but this increase is triggered by the body’s physiological response during exercise and is not considered as a pathological response. Conclusions. According to the findings of the study, physical exercise has been proven to elevate the risk of heart muscle damage by triggering an increase in cardiac troponin (cTn). However, this feature occurs in a physiological state and represents an exercise adaptation process. An analysis of the relevant articles reveals that this increase in cardiac troponin (cTn) has not been shown to have a negative influence on developing cardiovascular disease.